The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.freeradbiomed.2021.02.009
|View full text |Cite
|
Sign up to set email alerts
|

A useful and sensitive marker in the prediction of COVID-19 and disease severity: Thiol

Abstract: Thiol-disulphide homeostasis (TDH) is a new parameter indicating oxidative stress that plays a role in the pathogenesis of various clinical disorders. Our study planned to investigate TDH in COVID-19 patients. Age and gender-matched healthy subjects (n=70) and COVID-19 patients (n=144) were included in the study. In addition to the routine laboratory parameters of the groups, their native thiol (NT), total thiol (TT) and disulphide levels were measured. Primarily, we compared COVID-19 patients to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 27 publications
4
33
0
1
Order By: Relevance
“…No significant change was found in the disulphide levels between the pre- and post-treatment values. A similar finding reported no significant change in the disulphide levels in severe COVID-19 patients compared to healthy controls ( Kalem et al, 2021 ). Collectively, these findings imply that endogenous thiol contents are depleted and dynamic thiol/disulphide homeostasis is modified by COVID-19.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…No significant change was found in the disulphide levels between the pre- and post-treatment values. A similar finding reported no significant change in the disulphide levels in severe COVID-19 patients compared to healthy controls ( Kalem et al, 2021 ). Collectively, these findings imply that endogenous thiol contents are depleted and dynamic thiol/disulphide homeostasis is modified by COVID-19.…”
Section: Discussionmentioning
confidence: 61%
“…This data supports the results presented by Erel et al (2020) , who reported that thiol status is depleted in COVID-19 patients. Kalem et al (2021) also demonstrated that COVID-19 patients had lower native thiol and total thiol levels compared to healthy controls. Thiols are an independent risk factor for COVID-19 severity ( Erel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“… 22 , 23 Only little information was available about the relationship between oxidative stress and COVID-19 disease. 24 , 25 SARS-CoV-2 enters the host cell mainly via the cell surface enzyme angiotensin-converting enzyme 2 (ACE2), which plays a pivotal role in the conversion of angiotensin II (ANG II) to ANG-(1–7). The interaction of Ang-(1–7) with its receptor Mas plays an important role in the balance between reactive oxygen species (ROS) production and antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Although the contribution of oxidative stress to disease pathogenesis had been explored in several viral infection [ 28 , 29 ], its relevance to COVID-19 respiratory infection deserves more attention [ 25 , 26 ]. This is due to the fact that immune derangement during SARS-CoV-2 infection could switch on a lethal cycle of oxidative stress, inflammation and lung tissue injury.…”
Section: Introductionmentioning
confidence: 99%